KAJIAN FAKTOR DEMOGRAFI TERHADAP KEPUASAN PASIEN JAMINAN KESEHATAN NASIONAL PADA FASILITAS KESEHATAN TINGKAT PERTAMA - Putu Dyana Christasani; Satibi Satibi (Universitas Sanata Dharma, 2016)
The National Health Insurance (JKN), an Indonesian health care system, has been organized by BPJS Kesehatan using health care assurance mechanism. JKN system gave its service in collaboration with the existing health facilities throughout Indonesia. Primary health facilities named Puskesmas and Klinik Pratama, were playing role as the gate keeper of JKN system in order to provide basic health services optimally. The JKN participants' satisfaction could be used as the indicator for measuring the success rate of the JKN system. The patient demographics was being one of several factor affecting the JKN participants' satisfaction. This study aimed to examine the relationship between patient demographics and JKN participants' satisfaction in Puskesmas and Klinik Pratama located in Sleman, Bantul and Yogyakarta city. This research performed the descriptive analytic using cross sectional survey design. The patients's demographics examined in this study were patients' age, patients' gender, patients' education, patients' employment, patients' income, and membership status. The data taken quantitatively using questionnaires and equipped with qualitative data from interviewing the patients to obtain all the possible findings in the field. Sampling techniques for primary health facilities was performed by random sampling with total sample of 55 health facilities and purposive sampling with a total sample of 150 respondents. Data were analyzed using Chi-Square method to obtain the relationship between patient demographics and JKN participants' satisfaction. The results showed that patient's employment, patient's income, and membership status were significantly related to the JKN participants' satisfaction in Puskesmas and Klinik Pratama.